2016
DOI: 10.1136/bmjresp-2016-000145
|View full text |Cite
|
Sign up to set email alerts
|

Managing complex respiratory patients in the community: an evaluation of a pilot integrated respiratory care service

Abstract: IntroductionIn the UK, there is significant variation in respiratory care and outcomes. An integrated approach to the management of high-risk respiratory patients, incorporating specialist and primary care teams' expertise, is the basis for new integrated respiratory services designed to reduce this variation; however, this model needs evaluating.MethodsTo evaluate an integrated service managing high-risk respiratory patients, electronic searches for patients with asthma and chronic obstructive pulmonary disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 15 publications
0
28
0
2
Order By: Relevance
“…Two UK research studies on specialist clinics published from 2010 onwards were identified from the mapping review. 219,220 One of the clinics was for patients with hypertension 219 and one was for high-risk respiratory patients with COPD or asthma. 220 The research studies were both quantitative: one was a RCT 219 and the other was an uncontrolled observational study.…”
Section: Number and Type Of Uk Studies Identifiedmentioning
confidence: 99%
See 3 more Smart Citations
“…Two UK research studies on specialist clinics published from 2010 onwards were identified from the mapping review. 219,220 One of the clinics was for patients with hypertension 219 and one was for high-risk respiratory patients with COPD or asthma. 220 The research studies were both quantitative: one was a RCT 219 and the other was an uncontrolled observational study.…”
Section: Number and Type Of Uk Studies Identifiedmentioning
confidence: 99%
“…219,220 One of the clinics was for patients with hypertension 219 and one was for high-risk respiratory patients with COPD or asthma. 220 The research studies were both quantitative: one was a RCT 219 and the other was an uncontrolled observational study. 220 A summary table of the included studies is provided (see Appendix 4, Table 31).…”
Section: Number and Type Of Uk Studies Identifiedmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Integrated care models incorporating specialist respiratory and primary care expertise are associated with improved outcomes, including fewer hospital admissions and better attendance for pulmonary rehabilitation. 6,7 These have focused on primary care interventions carried out by medical and nurse practitioner staff in the patient's home or within the clinic setting. Such models could include behavioral health specialists to train and supervise primary health care staff and deliver clinical interventions to more complex patients.…”
mentioning
confidence: 99%